Voltammetric sensor for amoxicillin determination in human urine using polyglutamic acid/glutaraldehyde film - Santos, Daniela P. [UNESP]; Bergamini, Marcio F. [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier B.V. Sa, 2008)
A voltammetric sensor for determination of amoxicillin (AMX) was developed based on a glutaraldehyde cross-linked polyglutamic acid modified glassy carbon electrode. The proposed method is based on pre-concentration of AMX by cathodic accumulation as its oxidative product before being determined indirectly at potential as low as +0.23 V by square wave voltammetry. Linear response range, sensitivity and limit of detection were 2.0-25.0, 1.06 and 0.9.2 mu mol L-1, respectively, for AMX in 0.1 mol L-1 acetate buffer pH 5.2, pre-accurnulation time of 60s and accumulation potential of +1.0V. It was demonstrated that the glassy carbon electrode modified with PGA/GLU could be used for AMX determination in human urine without any separation step. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: sensor voltammetric; films of polyglutamic acid; amoxicillin; human urine